Evaluation of genetic damage in human peripheral lymphocytes exposed to mineral trioxide aggregate and Portland cements - Braz, Mariana Gobbo [UNESP]; Camargo, E. A.; Salvadori, Daisy Maria Favero [UNESP]; Marques, MEA; Ribeiro, D. A. (Blackwell Publishing, 2006)
Mineral trioxide aggregate (MTA) and Portland cement are being used in dentistry as root-end-filling material for periapical surgery and for the sealing of communications between the root canal system and the surrounding tissues. However, genotoxicity tests for complete risk assessment of these compounds have not been conducted up to now. In the present study, the genotoxic effects of MTA and Portland cements were evaluated in peripheral lymphocytes from 10 volunteers by the alkaline single cell gel (comet) assay. The results pointed out that the single cell gel (comet) assay failed to detect the presence of DNA damage after a treatment of peripheral lymphocytes by MTA and Portland cements for concentrations up to 1000 mu g mL(-1). In summary, our results indicate that exposure to MTA or Portland cements may not be a factor that increases the level of DNA lesions in human peripheral lymphocytes as detected by single cell gel (comet) assay.
Keywords: mineral trioxide aggregate; Portland cement; genotoxicity; comet assay